2021
DOI: 10.1088/1742-6596/1934/1/012023
|View full text |Cite|
|
Sign up to set email alerts
|

Verification of induction zone models for wind farm annual energy production estimation

Abstract: Fast engineering wake models are the backbone of wind farm annual energy production (AEP) estimators, whereas the addition of induction zone models in existing tools is a more recent response to rising concerns over wind farm blockage associated losses. Here, “blockage” describes the combined induction fields of all wind turbines inside a farm. Unlike the term might suggest, blockage not only reduces flow speeds, but also increases them; for instance along the outer edges of wind farms. Evaluating the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…There is no consensus today on how to model those effects, although, several approaches were developed with that objective [10]- [14]. Different modelling directly impacts the estimate for induction (and speed-up), as detailed in [15], [16], and the resulting magnitude blockage losses can differ by a factor ten depending on the selected approach [17]. Validation material remains limited, on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus today on how to model those effects, although, several approaches were developed with that objective [10]- [14]. Different modelling directly impacts the estimate for induction (and speed-up), as detailed in [15], [16], and the resulting magnitude blockage losses can differ by a factor ten depending on the selected approach [17]. Validation material remains limited, on the other hand.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study is limited to RANS simulations, the results also have implications for engineering models designed to predict blockage effects. These models are often potential flow-type models [11], which do not account for shear or atmospheric stability effects. As demonstrated in the Results section, the neglect of these effects, particularly atmospheric stability, can lead to material errors and likely bias in turbine interaction predictions.…”
Section: Engineering Models For Blockagementioning
confidence: 99%
“…Most engineering tools used to predict blockage (see [11] and references within) neglect the potential impact of shear on the results. To assess the effect of this simplification, Case 4 was repeated with a slip wall replacing the no-slip ground and uniform inflow replacing the Richards-Hoxey profiles.…”
Section: Effect Of Neglecting Shear/interaction With the Groundmentioning
confidence: 99%
See 1 more Smart Citation
“…For the AEP calculation and the wake modeling involved in the simulations, TOPFARM relies in PyWake (Pedersen et al, 2019), another DTU open source Python library that offers fast AEP evaluation from a range of engineering wake models. Recent works using TOPFARM (Ciavarra et al, 2022;Riva et al, 2020), and PyWake (Rodrigues et al, 2022;Fischereit et al, 2021;Forsting et al, 2021;Pedersen et al, 2021;Quick et al, 2022) can be found in the literature.…”
mentioning
confidence: 99%